La Evolución Del Movimiento Cooperativo Desde Su Origen Hasta La Actualidad A Través De Su Máximo Exponente: La Sociedad Cooperativa - Belmonte, Jesús López; Guerrero, Antonio José Moreno; Cabrera, Arturo Fuentes (European Scientific Journal, ESJ, 2018)
Cooperativism refers to the union of fellows for the benefit of the community. Cooperatives as social entities refer to those that form a group to reverse both employment and economic situation. Their focus is on the generation of jobs and the satisfaction of its members. In Europe, cooperativism has its appearance in the S. XIX as a result of the wave of dismissals that resulted to the industrial revolution. Majorly, the first cooperatives were made by professionals of the agrarian sector, until this present time where there are practically cooperatives in each economic sector. Due to its expansion, its values and ideology, there has been a broad legislative development. This began from its inception to this present day, and it involves the creation of the ICA (International Cooperative Alliance) as an organization representative of this movement. This paper focuses on understanding the evolution of cooperativism which stems from its appearance as a term and mass social movement to this present day. For this present study, we used a research model framed in the qualitative paradigm and that was focused on descriptive aspects. This is in regards to both content analysis and comparative methodology. We extracted very enriching results as a result of an extensive and deep bibliographic search in different repositories and sources of information. It has allowed us to compile the main theoretical concepts that encompass cooperativism from its conceptual delimitation, history, and most outstanding milestones to the typology of cooperative entities, exporting values, legislative development, and recent business-level data.